2018
DOI: 10.30638/eemj.2018.123
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Vehicle Emission on Mainline Freeway Under Isolated and Integrated Ramp Metering Strategies

Abstract: On freeways with multiple on-ramps, it is a common practice to design a ramp metering strategy so as to regulate the entering rates from ramps and minimize the disruptions on the mainline. Most of the existing studies examine the performance of ramp metering on mobility and safety, rather than their impacts on the environment. This paper focuses on the estimates of vehicle emissions along mainline freeways under various ramp metering strategies. Vehicle speed and acceleration rates were measured during a field… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 0 publications
0
24
0
Order By: Relevance
“…As an industry that recently stood on the cusp of the era of the Internet of Things (IoT) and consumerism, the fresh ecommerce business has gained increasing attention [1][2][3][4][5]. Of all the critical factors that play a role in the production and operation management of a fresh ecommerce business, cold chain logistics has been proved to be the key process that determines its profitability and competitiveness [6,7]. Since the construction of the cold chain logistics infrastructure network in the fresh ecommerce industry is still nascent, there are problems that business managers cannot ignore.…”
Section: Introductionmentioning
confidence: 99%
“…As an industry that recently stood on the cusp of the era of the Internet of Things (IoT) and consumerism, the fresh ecommerce business has gained increasing attention [1][2][3][4][5]. Of all the critical factors that play a role in the production and operation management of a fresh ecommerce business, cold chain logistics has been proved to be the key process that determines its profitability and competitiveness [6,7]. Since the construction of the cold chain logistics infrastructure network in the fresh ecommerce industry is still nascent, there are problems that business managers cannot ignore.…”
Section: Introductionmentioning
confidence: 99%
“…Other scholars combined Bayesian network methods to study the selection of green suppliers in agricultural production [5]. In one study, an integrated metring strategy was adopted to estimate instant vehicle emissions by measuring the speed and acceleration of vehicles on slopes, thus improving the study on the impact of ramp metring on the environment [6]. In another study, scholars applied an improved whale optimization algorithm and proposed an algorithm framework for the location model of electric vehicle charging stations based on the calculation of a large number of examples [7].…”
Section: Introductionmentioning
confidence: 99%
“…Bae et al [7] adopted ramp metering to evaluate the changes in traffic flow and CO 2 emission variations, which suggested that ramp metering makes a great contribution to the reduction of CO 2 emissions. Du et al [8,9] found that the isolated and integrated ramp metering approaches can improve mobility and reduce travel delay. However, relevant studies are limited and emissions vary with vehicle type.…”
Section: Introductionmentioning
confidence: 99%